Retreatment with full-dose cytarabine in a patient with previous neurological toxicity. (October 2022) - Casasnovas, Núria Meca; Manzaneque, Alba; Muntañola, Ana; Castells, Genís
Introduction: Cytarabine is one of the main chemotherapy drugs used to treat hematological malignancies. Neurotoxicity is an increasingly recognized adverse effect of high-dose cytarabine therapy and occurs in 10% to 25% of patients. There is very little experience with cytarabine retreatment following neurotoxicity. Case report: We report a case of a man who was diagnosed with chemotherapy-induced cerebellar syndrome. He was treated with high doses of cytarabine. Management and outcome: The patient was successfully retreated at full dose after experiencing cytarabine-induced cerebellar toxicity during the first cycle of a chemotherapy regimen. He did not develop any neurological complications and successfully underwent hematopoietic stem cell transplantation. He is currently in complete remission and free of disease. Discussion: This original case report assesses the possibility of retreatment without the need for dose reduction.